2018
DOI: 10.1016/j.visres.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

EEG frequency tagging reveals higher order intermodulation components as neural markers of learned holistic shape representations

Abstract: Shape perception is intrinsically holistic: combinations of features give rise to configurations with emergent properties that are different from the sum of the parts. The current study investigated neural markers of holistic shape representations learned by means of categorization training. We used the EEG frequency tagging technique, where two parts of a shape stimulus were 'tagged' by modifying their contrast at different temporal frequencies. Signals from both parts are integrated and, as a result, emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…As the fifth harmonic of f 2 overlapped with the sixth harmonic of f 1, both at 36 Hz, we included only four harmonics for further analysis. For intermodulation responses, we analyzed various frequencies ( nf 1 ± mf 2, where n and m are integers) following previous studies (e.g., Vergeer et al., 2018). At f 2 −f 1 = 1.2 Hz, there was no clear response in the spectrum (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the fifth harmonic of f 2 overlapped with the sixth harmonic of f 1, both at 36 Hz, we included only four harmonics for further analysis. For intermodulation responses, we analyzed various frequencies ( nf 1 ± mf 2, where n and m are integers) following previous studies (e.g., Vergeer et al., 2018). At f 2 −f 1 = 1.2 Hz, there was no clear response in the spectrum (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Such intermodulation responses cannot be explained solely by the inputs at f1 and f2 but can only be a result of nonlinear interactions between the input frequencies (Regan & Regan, 1988; see Gordon et al, 2019 for a recent review). By employing the frequency-tagged SSVEP technique, previous studies showed that the intermodulation response was observed when parts were bound into holistic representations such as faces (Boremanse et al, 2013(Boremanse et al, , 2014, Gestalt formation (Aissani et al, 2011;Alp et al, 2016;Gundlach & Mu¨ller, 2013), and newly learned shapes (Vergeer et al, 2018). For example, Boremanse et al (2013) frequency-tagged the left and the right half of face stimuli at different frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…3and 4for TF conditions f TARGET ≠ f MASK (three f MASK frequencies each above and below f TARGET ), using values of τ 0 , τ 1 and n estimated from the fits to data from Experiment 1 and using L amp (f TARGET ) estimated from the mask-only grating condition from Experiment 2. Values of f MASK were in [10,12,14,18,20,22] for f TARGET = 16 Hz, and in [5,6,7,9,10,11] for f TARGET = 8 Hz. For each electrode and response condition, we estimated tuned suppression parameters α and β using ordinary least-squares fits, allowing α and β to vary over the entire range.…”
Section: Mask Targetmentioning
confidence: 98%
“…Many studies have used IM components to study stimulus interactions 10,11,15,16,38 . When we analyzed the IM components at 2|F TARGET − F MASK | using a similar approach as above, we did not observe more suppression at low masking frequencies, but instead observed inconsistent suppression for mask frequencies very close to the target ( Supplementary Fig.…”
Section: Tf Suppression Is Low Frequency Tuned To Distinguish Betweementioning
confidence: 99%
See 1 more Smart Citation